Impact of perinatal factors on T cells and transcriptomic changes in preterm infant brain injury - Xiaoli Zhang; Yu Yang; Yiran Xu; Liuji Chen; Ming Niu; Jinjin Zhu; Shan Zhang; Yanan Wu; Bingbing Li; Lingling Zhang; Juan Song; Falin Xu; et al. (Journal of Neuroinflammation)
Abstract Background T cells have been implicated in various neurological conditions, yet their role in neonatal brain injuries remains unclear. This study aimed to investigate the impact of perinatal factors on frequencies of T cell subsets in preterm infants and to explore the differences in blood genome expression profiles between preterm infants with and without brain injury. Materials and methods Three cohorts of preterm infants were used. Blood samples were collected soon after birth for the first cohort and late timepoint for the second and third cohorts. In the first cohort (88 infants), flow cytometry measured the proportions of αβT and γδT cell subsets in peripheral blood, analyzing associations with gestational age, birth weight, sex, delivery type, and maternal conditions. The second cohort focused on the relationship between T cell subsets and brain injury. In the third cohort, transcriptome sequencing identified differentially expressed genes and pathways in infants with brain injury, highlighting immune-related changes. Results Infants born at 29–30 weeks or with a birth weight of 1000–1500 g had significantly higher proportions of Vδ2+ T cells compared to those born at 30–32 weeks or with a birth weight > 1500 g, while no significant difference was found between infants born at < 29 weeks or with a birth weight < 1000 g. A negative correlation was observed between gestational age and Vδ2+ T cell frequency. No significant associations were found between Vδ2+ T cell proportions and perinatal factors other than gestational age or brain injury. Blood transcriptome analysis revealed 173 differentially expressed genes, characterized by downregulated interferon signaling and upregulated antimicrobial and neutrophil pathways in infants with brain injury. Conclusions Gestational age and birth weight influence Vδ2+ T cell proportions in preterm infants, likely reflecting immune maturation. While no direct link to brain injury was found, altered immune pathways suggest potential biomarkers for prognosis, warranting further research into their roles and therapeutic implications in neonatal brain injuries.